Ефективність роботи мобільних електрифікованих засобів сільськогосподарського призначення - Мельник, Р. В.; Melnyk, Roman (КНТУ, 2015)
В статті приведенні результати попередніх досліджень експериментального зразка електротрактора ХТЗ-2511Е а також встановлено, що на сьогоднішній день набувають широкого розповсюдження електродвигуни вентильного типу для електротранспорту через високий ККД до 95% та можливістю програмування контролера на різну напругу та різні режими роботи. Improving the operational efficiency of mobile power facilities for agricultural through the use of electricity. Analysis of the previous research was based on the study of scientific and technical information in the field of mobile power on electric-battery drive. Found that currently the ventilated electronic motors for electric transport become widespread because of high propulsive efficiency up to 95% and programmable controller for different voltages and different modes of operation. The developed experimental model of elektric traktor HTZ- 2511E which time of work without recharging batteries is up to 5 hours on transport works. Mobile power facilities based on electric-battery drive in agriculture will increase the efficiency of the machine and tractor units in interpreting the application of the system motor in wheel. Considering the strong potential of JSC "Kharkiv Tractor Plant" and the high level of the electricity sector, Ukraine has good conditions for the solution in the short term all technical issues and successful implementation in the production of tractors with electric-battery drive.
The effectiveness of mobile power facilities for agriculture servise
Keywords: мотор-колеса; мобільно енергетичні засоби; трактор; електродвигун; тягова характеристика; електроакумуляторнний привод; motor in wheel; mobile power facilities; tractors; electric motor; traction; electric-battery drive